Cupido-Putto oder Weltmacht Eros?: Der Calvinist Theobald Hock (1573-ca. 1623) wider den habsburgischen Hofkomponisten Jacob Regnart (1540-1599) ; zur Kontroverse um die Konzeption des göttlichen “Amor” in der geselligen Lyrik um 1600 - Kühlmann, Wilhelm (Daphnis, 2023)
Abstract The Calvinist politician and diplomat Theobald Hock (1573-ca. 1623) published in his collection Schönes Blumenfeld (1601) the poem “Das Cupido kein Kindt sey” (Cupid is not a child). Hitherto hardly noticed, it is a clear palinody to one of the most famous song poems of the epoch, to “Venus du und dein Kind” (Venus you and your child) written by the Kapellmeister and poet-composer Jacob Regnart († 1599) who was in Habsburg service. Both authors lived in Prague for a short time before 1599. Hock did not protest primarily against the use of pagan mythologems, as did some Christian rigorists (such as J. Rist), but (in a critical obituary of his Catholic neighbour?) Hock polemically dismisses Regnart’s text as a document of a foolish superstition that was widespread even among the educated. He replaces it with a conception of an omnipotent Eros that goes back to Hesiod and Plato, apparently mediated by rinascimental Platonism (M. Ficino), and which accompanies and drives all creations, including man’s cultural and moral achievements. Hock thus joins critical questions that the puerile figure of the naked Cupid/Amor had also provoked elsewhere (for example in the emblem book of Andreas Alciatus).
Gesehen am 18.09.2023
Keywords: Regnart, Jakob; Hock, Theobald